2018
DOI: 10.1007/s10096-018-3341-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Clostridium difficile infection in adult oncohaematological patients: experience from a large prospective observational study

Abstract: The aim of the study is to evaluate demographics, epidemiology, clinical characteristics, treatment and outcomes of Clostridium difficile infection (CDI) in patients with and without concurrent cancer. This is a prospective cohort study of consecutive primary CDI episodes in adults (January 2006-December 2016). CDI was diagnosed on the presence of diarrhoea and positive stool testing for toxigenic C. difficile. Univariate analysis assessed differences between cancer and non-cancer patients. Risk factors of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 40 publications
9
7
1
Order By: Relevance
“…Advanced age is recognised as a risk factor for CDI in cancer and non-cancer patients 24. The age differed among our cohort, with patients with haematological malignancies being younger while non-cancer patients were older than patients with solid tumours, which is in line with some other studies 12 18 25 26…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Advanced age is recognised as a risk factor for CDI in cancer and non-cancer patients 24. The age differed among our cohort, with patients with haematological malignancies being younger while non-cancer patients were older than patients with solid tumours, which is in line with some other studies 12 18 25 26…”
Section: Discussionsupporting
confidence: 90%
“…In our cohort, cancer patients were more exposed to antibiotic use than non-cancer patients, but the exposure was very high (>90%) in both groups. In contrast, the study by Larrainzar-Coghen et al showed similar exposure to antibiotics prior to CDI between cancer and non-cancer patients (82.7% and 86.7%, respectively) 18. The most frequently used antibiotics in our study were fluoroquinolones and cephalosporins of the second and third generation, but there was no difference in exposure between cancer and non-cancer patients.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations